Inhibition of Human Immunodeficiency Virus Type 1 (HIV-1) Replication by a Two-Amino-Acid Insertion in HIV-1 Vif from a Nonprogressing Mother and Child - Alexander, Louis (American Society for Microbiology, 2002)
We studied a 15-year-old girl, patient X, who has maintained consistently low plasma loads of human immunodeficiency virus type 1 (HIV-1) RNA, as well as normal and stable CD4(+) T-cell concentrations. She has presented no clinical manifestations of AIDS, despite having only received zidovudine monotherapy for a part of her life. Patient X's HIV-positive mother (patient Y) has also not progressed to AIDS and has never been treated with antiretroviral agents. HIV-1 isolated from patient X replicated poorly in human peripheral blood mononuclear cells (PBMC). In order to map the determinant of the poor growth of patient X's isolate, viral sequences from patient X were determined and examined for insertion or deletion mutations. These sequences contained a two-amino-acid insertion mutation in the Vif gene, which was also observed in uncultured PBMC acquired at different times. Furthermore, Vif sequences harbored by patient Y contained the identical mutation. These observations suggest that polymorphic HIV-1 was transmitted to patient X perinatally 15 years previously and has been maintained since that time. Recombinant HIV-1, engineered with Vif sequences from patient X, replicated in PBMC to levels approximately 20-fold lower than that of wild type. Removal of the insertion mutation from this recombinant restored replication efficiency to wild-type levels, while introduction of the insertion mutation into wild-type Vif sequences resulted in greatly decreased replication. Furthermore, Vif protein from patient X's HIV-1 was aberrantly cleaved, suggesting a mechanism for loss of Vif function. Since HIV-1 containing these sequences replicates poorly, the implication is that the two-amino-acid insertion mutation in Vif contributes significantly to the nonprogressor status of this mother and child. Further studies of these sequences might provide information regarding contributions of Vif structure and/or function to HIV-1 virulence.